Pengaruh Keamanan Produk, Digital Marketing dan Motivasi Terhadap Omset Penjualan - Rinda Asytuti; Luhhinar Windy Astuti (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2021)
The safety of a product is the initial asset of a product that can be marketed. Especially for skincare products that have become the daily consumption of women and men. Security guarantees must be very concerned by consumers. A person before making a decision to join a business must also pay attention to the safety of the products to be sold, so that product safety becomes an important element in running a business. To start marketing products, members must also master digital marketing so that the product targets are in accordance with consumer interests. This study aims to determine the effect of product safety, digital marketing, and motivation on sales turnover of gbee glow beauty skincare members. This study uses a quantitative approach. The data collection method in this study used a questionnaire (questionnaire) with a sample of 60 respondents who were members of skincare gbee glow beauty in Pekalongan Regency. The sampling technique used is the purposive sampling method.